Validation of the Theoretical Framework for Adoption of Accounting Information System Using Structural Equation Modelling - Khalil Mesbah, Abdul Jalil; Yuserrie, Zainuddin (Penerbit Universiti Malaysia Pahang, 2015)
The purpose of this study is to investigate the effect of perception and beliefs of information technology (IT) users on the perspective of accounting information system adoption in the SMEs of Libya An integrated theoretical model was developed for the adoption of accounting information system by applying wide range of technological situation aligned with attitude of technology users. The study is based on quantitative survey with 348 respondents in small and medium enterprises of Libya. The finding of the study confirms the validation of the theoretical model developed and verifies the issues of common method bias. This paper is one of the few researches to determine the technological acceptance concept focusing on advancement of business strategy.